The Influence of Price and Promotion on Sales Volume of BumDes Shelter House Business in Sungai Rebo Village - Ranti Apriyanti; M.Amirudin Syarif (Budapest International Research and Critics University, 2022)
Marketing is a business function that deals directly with consumers. Some mistakes in pricing strategy will affect the company's sales volume. Some mistakes in pricing strategy will affect the company's sales volume. The company is expected to provide information about the benefits that will be obtained from the products offered to consumers. BumDes Singa Rebo shelter market share is used to analyze the target market for a product. To analyze the level of market share using the level of consumer purchasing decision behavior. The Bumdes has not yet reached the market in all regions in South Sumatra. This is because the company's strategy has not penetrated the market by relying on distribution and promotion channels to remote areas. A good pricing strategy should be based on the marketing strategy that will be carried out by BumDes Singa Rebo so that its sales volume increases. The results of this study show that the price has an influence on sales volume which has a positive sign. Price contributes 47.7%, while the remaining 52.3% is influenced by other factors not examined in this study, such as promotion factors, marketing management and others.